UEC signs a general agreement with Indian Institute of Technology, Varanasi. - (:unkn) unknown (The University of Electro-Communications, 2022)
On October 4, 2022, the University of Electro-Communications（UEC）signed a general agreement with Indian Institute of Technology, Varanasi（IIT-BHU）, to promote further international collaboration. The signing ceremony held online was attended by UEC President Tano, Director Abe from the Board of Directors, and three other UEC members. The ceremony began with the opening remarks by President Pramod Kumar Jain of IIT-BHU and President Tano. The signed agreements were presented after the introduction of the two universities. Following the signing ceremony, the members of IIT-BHU and UEC exchanged ideas for further research and student exchange. Indian Institute of Technology, Varanasi, is one of India's 23 national universities specializing in engineering, science, and technology. Although the entrance examinations are unified, each school operates with its own autonomous organization. They are research institutions of national importance and are internationally recognized for their high level of research. We look forward to further development of educational and research exchanges in the future.
Keywords: UEC; agreement; University of Electro-Communications; collaboration